Proof of the conjecture of Keskin, Siar and Karaatli - Rachid Boumahdi; Omar Kihel; Sukrawan Mavecha (My University, 2018)
prove the conjecture of Keskin, Şiar and Karaatlı on the Diophantine equation x 2kxy + y 2 -2 n = 0.
Keywords: Linguistics and Cultural Studies